A comparative study to assess knowledge regarding tobacco use and its ill effects among school children of district Sirmour Himachal Pradesh - Verma, Kavita; Sharma, Anjali; K., Anupama (International Journal Of Community Medicine And Public Health, 2021)
Background: Drug addiction is one of the major problems across the globe. It is seen in various forms like marijuana, tobacco, hashish, cannabis and heroine etc. especially tobacco being the most common. The objective of the study was to assess the knowledge regarding tobacco use and its ill effects among school children of district Sirmour Himachal Pradesh. The objective of this study was to assess the knowledge regarding use of tobacco and ill effects among school children. Methods: The school going (9th-12th standard) boys and girls were taken as study sample. The convenient sampling technique was used. Results: The study findings showed that the pre-test score of girls and boys are different i.e. 49% of girls had excellent pretest score while 56% boys are had excellent pretest knowledge and 51% of girls and 39% of boys had good knowledge where as 5% of boys had average knowledge score. The post-test score findings shows that 43.1% of girls had excellent knowledge, 27.5% of girls had good knowledge and 4.6% of girls had average knowledge while the post-test score of 53.2% of boys had excellent, 16.5% of boys had good and 5.5% of boys had average level of knowledge. The t value 4.264 was found to be highly significant among adolescent boys. Conclusions: This study provides insight into the factors to consider while planning adolescent anti-smoking programs in this and similar settings.